Biogenic deterioration of concrete and its mitigation technologies - Noeiaghaei, T.; Mukherjee, Abhijit; Dhami, N.; Chae, S. (Elsevier BV, 2017)
Concrete is used in great volumes for construction of buildings, roads, sewer systems, marine structures, bridges, and tunnels. Although chemical degradation is regarded as the major cause of their deterioration, recent research has revealed important role of biogenic deterioration. In particular, biogenic deterioration is a serious problem in sewer systems, subsea pipelines, bridge piers, oil and gas pipelines, and offshore platforms. Recently, nanomaterial-embedded concrete and nanomaterial-incorporated coatings with novel functionalities such as self-protection and anti-corrosion ability have been successfully developed for prevention and control of concrete deterioration. This paper presents an overview of both existing control measures and recent progress on development of nano-enabled approaches for protection of concrete structures against biogenic deterioration.